Assessment of the Impact of Betulin on the Immune Status of Cows with Leukemia-Associated Infection - Vlasenko , Vasily; Pleshakova, Valentina; Bayseitov, Sayat; Lescheva, Nadezhda (KnE Life Sciences, 2021)
This study examined the immunity dynamics of bovine brucellosis-complicated leukemia, as well as the efficacy of treatment with betulin. Blood serum samples were taken from cows with specific brucellosis antibodies and bovine leukemia virus antibodies based on the results of complex diagnostic studies. Animals (n = 5) selected based on serological studies were injected subcutaneously with betulin-PEG three times with an interval of 7 days at a dose of 10 mg/kg. Blood was taken for hematological and immunological studies before the injection, and after the first, second and third injections. It was found that leukemia and brucellosis infections were accompanied by a significant increase in the number of leukocytes and lymphoid cells, as well as strong fluctuations in the leukocyte functional and metabolic activity parameters (from insignificant in some individual animals to significantly increased in others). Immunological restructuring of the body after triplicate administration of betulin-PEG was characterized by the restoration of the number of lymphoid cells to the level of clinically healthy animals, as well as a significant increase in the functional and metabolic activity of the neutrophilic granulocytes, especially their oxygen-dependent systems. Based on the results, the product is recommended as an effective means to restrain the leukemia process that is complicated with associated infection, as well as to use for seronegative animals in order to increase nonspecific resistance to BLV infection. Keywords: leukemia, brucellosis, cattle, immune status, betulin, immunocorrection, associated infection